Disrupted functional connectome in a rodent model of autism during social isolation - Kemecsei, Robert Gergely; Dániel-Papp, Szizel; Balazs, David Barnabas; Ghebrihiwet Tewelde, Estifanos; Csillag, Andras; Zachar, Gergely (Frontiers in Neural Circuits, 2025)
Autism spectrum disorder (ASD) is associated with disruptions in social behavior and the neural circuitry behind it. Very little data is available on the mechanisms that are responsible for the lack of motivation to reunite with conspecifics during isolation. It is as important to investigate the neural changes that reduce motivation to end social isolation, as those underlying the reactions to social stimuli. Using a rodent model of prenatal valproic acid (VPA) exposure, we investigated how social isolation affects the neural activation of key brain nuclei involved in social processing and stress regulation. Juvenile male C57BL/6 mice were treated prenatally with VPA or saline (CTR) and subjected to 24 h of social isolation from their cage mates, with neural activity assessed via c-Fos immunohistochemistry. Based on correlational activations we reconstructed and analyzed the functional connectome of the observed brain regions. Control animals exhibited elevated c-Fos expression in the regions central to the mesolimbic reward system (MRS), social brain network (SBN), and stress-related networks, with the interpeduncular nucleus (IPN) at the core, compared to VPA-treated animals. Functional network analysis revealed a more widespread but less specific pattern of connectivity in VPA-treated animals. These findings suggest that prenatal VPA exposure disrupts certain neural circuits related to social behavior and stress regulation, offering an insight into the altered perception of social isolation in ASD models, and highlighting potential therapeutic targets.